ANALISIS SWOT DALAM MENENTUKAN STRATEGI PROMOSI DESA WISATA MANDING PADA ERA ADAPTASI KEBIASAAN BARU - Dwi Agus Kristianto; Dea Riskita Radanis (Kepariwisataan: Jurnal Ilmiah, 2023)
It has been two years since the world has been shocked by the presence of a highly contagious virus. COVID-19 is a disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The tourism industry has also been affected. Tourism as a Strategic Economic Sector, during the COVID-19 pandemic experienced a crisis. The Manding Tourism Village felt the same way. It has been almost two year that the economic conditions of the residents who sell in the Manding Tourism Village have fluctuated due to the pandemic. Therefore, it is necessary to form a promotional strategy to help the local people's economy. This study aims to determine the promotional strategies used by Manding Tourism Village in the era of adapting new habits in the Special Region of Yogyakarta. The research method used is descriptive-qualitative. Data sources come from direct observation, semi-structured interviews, documents, and triangulation. The results of the study describe that Manding Tourism Village has not used the right promotion strategy, both digital and conventional. At the end of the study, the author provides suggestions for promotional strategies that can be used by Manding Tourism Village, namely: a. The local government needs to be present to provide education or training related to digitization to the management and community of the Manding Tourism Village; b. Managers should improve by holding deliberation to discuss the regeneration of members; c. Facilities and infrastructure so that they can be used optimally; d. Carry out promotional activities both through conventional and digital media.